Health disparities, diversity, and inclusion context, controversies, and solutions - Rose, Patti Renee (Jones & Bartlett Learning, 2018)
The book highlights steps that key stakeholders, including federal, state, and private health care and public health entities, should take to ensure that representatives from emerging majority groups are involved with and serve as leaders in terms of the provision of health care at every level. Diversity is examined in terms of patient satisfaction and quality outcomes with an emphasis on racial, ethnic, gender, and linguistic diversity.